2024
DOI: 10.1021/acs.est.3c09451
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Pyrolysis of Halogen-Containing Plastics for Resource Recovery and Halogen Upcycling: A State-of-the-Art Review

Chuan Ma,
Shogo Kumagai,
Yuko Saito
et al.

Abstract: Plastic waste has emerged as a serious issue due to its impact on environmental degradation and resource scarcity. Plastic recycling, especially of halogen-containing plastics, presents challenges due to potential secondary pollution and lower-value implementations. Chemical recycling via pyrolysis is the most versatile and robust approach for combating plastic waste. In this Review, we present recent advancements in halogen-plastic pyrolysis for resource utilization and the potential pathways from "reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 175 publications
(284 reference statements)
0
2
0
Order By: Relevance
“…2–4 At present, this is mostly focused on the recovery or comprehensive utilization of wastes produced from a concrete chemical process. 5–8 However, few studies based on the potential reaction ability and special properties of wastes are reported.…”
Section: Introductionmentioning
confidence: 99%
“…2–4 At present, this is mostly focused on the recovery or comprehensive utilization of wastes produced from a concrete chemical process. 5–8 However, few studies based on the potential reaction ability and special properties of wastes are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several advancements have been achieved regarding the pyrolysis of halogen-plastics for resource recovery and potential routes for upcycling of halogens [213]. Microwave heating, plasma or electron beam irradiation, and supercritical pyrolysis are newly emerging industrially relevant technologies available for the dechlorination or breakdown of chlorinated plastics.…”
mentioning
confidence: 99%